Enterochromaffin-like (ECL) cells Hyperplasia in Fundic Gland Polyp and Its Association with the Usage of Proton Pump Inhibitors - Ening Krisnuhoni; Fili Sufangga; Diah Rini Handjari; Nur Rahadiani; Marini Stephanie (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2021)
-